Maternal mortality related to pregnancy-induced hypertension (pih) in a maternity in Pará - Diana Damasceno Guerreiro; William Dias Borges; Heliana Helena de Moura Nunes; Silvia Cristina Santos Silva; Juliana de Paula Maciel (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769213159 Objective: to investigate the prevalence of maternal mortality resulted by PIH in women hospitalized in a maternity ward of the state of Pará, in the period 2009-2012. Method: documentary, descriptive and retrospective research, with a quantitative approach in which the statistical analysis was done using the software BioeStat 5.0. Results: Out of 122 maternal deaths, 27% were by PIH, most women (48.5%) were between 20 to 29 years old, had incomplete primary education (39.4%), were in a stable union (48.5%), brown-skinned (60.6%), housewives (39.4%), and the death occurred in the puerperium (81.8%). Conclusion: It is recommended more attention to pregnant women with preeclampsia or potential to develop it, through more systematic monitoring and appropriate sharing in the Care Network. Moreover, it is pointed out the necessity of improving the socioeconomic determinants, revealing, thus, the importance of broad social and clinical-care interventions to improve these indicators as part of the Millennium Development Goals.